2009
DOI: 10.1038/hr.2009.96
|View full text |Cite
|
Sign up to set email alerts
|

Morning home blood pressure may be a significant marker of nephropathy in Japanese patients with type 2 diabetes: ADVANCED-J study 1

Abstract: A 3-year multicenter, prospective, randomized, open-label trial (ADVANCED-J) compared the effect of an increased dose of angiotensin-II receptor blocker (ARB) with that of a maintenance dose of ARB plus calcium channel blocker (amlodipine) on blood pressure (BP) control, nephropathy and atherosclerosis in patients with type 2 diabetes and hypertension in whom the usual ARB dose failed to control BP. A cross-sectional analysis using baseline data was conducted. Of 316 patients (recruited between September 2004 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…In a Japanese study of normotensive, lean patients with type 2 diabetes mellitus, BNP level was positively associated with UACR [5]. A positive association between BNP level and UACR was found in a Japanese study of 316 patients with type 2 diabetes mellitus [6]. In a Japanese study of 233 patients with type 2 diabetes mellitus, BNP level was positively associated with macroalbuminuria [7].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In a Japanese study of normotensive, lean patients with type 2 diabetes mellitus, BNP level was positively associated with UACR [5]. A positive association between BNP level and UACR was found in a Japanese study of 316 patients with type 2 diabetes mellitus [6]. In a Japanese study of 233 patients with type 2 diabetes mellitus, BNP level was positively associated with macroalbuminuria [7].…”
Section: Discussionmentioning
confidence: 80%
“…In previous epidemiological studies regarding the association BNP and renal function, plasma BNP ranged from 10.8 to 46.3 ng/dL [5][6][7][8][9]. The discrepancies among these studies may be explained, at least in part, by differences in sample size; the definition of renal function; characteristics such as age, sex, race, BMI, prevalence of coronary heart diseases, subclinical heart failure and hypertension; and other confounding factors.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, albuminuria has been directly linked to the risk of adverse cardiovascular outcomes and mortality, independent of other risk factors (Stephen et al, 2014), and may hence represent a potential target to improve cardiovascular and renal outcomes (Basi & Lewis, 2006;de Zeeuw, 2007;de Zeeuw et al, 2004;Holtkamp et al, 2011). Previous studies have indicated that significant predictors of progressive albuminuria include male sex, older age, obesity, hyperglycemia, hypertension, dyslipidemia, and baseline albuminuria (Bash, Selvin, Steffes, Coresh, & Astor, 2008;Jindal et al, 2013;Lin et al, 2009;Scheven et al, 2013;Tanaka et al, 2009). Moreover, a recent cross-sectional study, conducted among 9,579 middle-aged and elderly Chinese participants with normal urinary albumin excretion, reported that the UACR significantly correlated with metabolic syndrome and its components.…”
Section: Discussionmentioning
confidence: 97%
“…Clinical investigations of BNP have focused on its use in diagnosing heart failure and left ventricular hypertrophy and dysfunction 2,3) ; however, the Framingham Heart Study 4) demonstrated that plasma BNP levels predicted the risk of death and cardiovascular events in a community-based sample of individuals without heart failure. Thus, BNP has recently been well used in antihypertensive treatment to assess hypertensive target organ damage 5) and risk stratification 6) in patients without heart failure. Several studies 7,8) have demonstrated that antihypertensive treatment decreased plasma BNP levels and could be used as a biochemical marker of effective blood pressure control.…”
Section: Introductionmentioning
confidence: 99%